Fidel Castro in Sierra Maestra. Tour of a photograph (1958) - Camacho Navarro, Enrique (2020)
The Cuban revolution is a process in which the production of images is a fundamental part to explain its historical development. Through a photograph of Fidel Castro, captured by the Spanish photojournalist Enrique Meneses, the possibility of making a story is shown -in accordance with the proposal of John Mraz- with and over photographs. This iconographic representation, taken by Fidel Castro in the Sierra Maestra in the first months of 1958, and which was integrated into the edition of a book by the same photographer, offers a good opportunity to reflect on the contributions that iconology has in the Circumcaribe, and throughout Latin America.